Europe and the Asia Pacific - Brendan Nelson (European Centre for International Political Economy (ECIPE), 2012)
In this new policy brief Ambassador Dr Nelson describes a changing world order in which the Asia Pacific will come to play an even more influential role - economic activity will continue to grow as already five of the world's economic power houses - the US, China, India, Japan and Korea - are in the region. As economies grow, so do military expenditures and the consequences of any conflagration might bear huge costs for the world economy: all of Europe's exteuro700 billion North Asian trade passes through the South China Sea, and half of the world's energy passes through the Straits of Malacca. But the European Union can and should play a role in mitigating these dangers by strengthening bilateral ties with countries in the region, as well as multilateral ties through involvement with the ASEAN Regional Forum. The most important lesson offered by Ambassador Dr Nelson is that the nations of Europe should seek to engage with Asia. But ultimately, that will require Europeans to turn up and do so regularly in Asia, or else Asia may find Europe sooner than it thinks and in ways it might least expect. This policy brief is based of the speech Ambassador Dr Brendan Nelson gave at the ECIPE conference on the 31st of October with the same title.
Keywords: 330; Internationale Wirtschaftsbeziehungen; EU-Staaten; Asiatisch-pazifischer Raum; Meinung